Impact of payment system change from per-case to per-diem on high severity patient's length of stay. Issue 37 (September 2016) - Jang, Sung-In; Nam, Chung Mo; Lee, Sang Gyu; Kim, Tae Hyun; Park, Sohee; Park, Eun-Cheol
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: A new payment system, the diagnosis-related group (DRG) system, and Korean diagnosis procedure combination (KDPC, per-diem) payment system were officially introduced in 2002 and in 2012, respectively. We evaluated the impact of payment system change from per-case to per-diem on high severity patient's length of stay (LOS). Claim data was used. A total of 36, 240 case admissions and 72, 480 control admissions were included in the analysis. Segmented regression analysis of interrupted time series between cases and controls was conducted. Hospitals that consistently participated in the DRG payment system and changed to the KDPC payment system were defined as case hospitals. Hospitals that consistently participated in the DRG payment system were defined as control hospitals. LOS increased by 0.025 days per month ( P  = 0.0055) for 3 surgical diagnosis-related admissions due to the bundled payment system change. LOS among emergency admissions also increased and showed an increasing tendency under the KDPC. The LOS increase was observed specifically for complex procedure admissions and high severity cases (CCI 0, 1: 0.022, P  = 0.0142; CCI 2, 3: 0.026, P  = 0.0288; CCI ≥ 4: 0.055, P  = 0.0003). Although both payment systems are optimized to decrease LOS, incentives to reduce LOS are stronger under the DRG system than under the KDPC system. It is worth noting that too strong incentive for reducing LOS is suitable to high severity cases.